IMPLEMENTASI UNDANG-UNDANG NOMOR 10 TAHUN 2009 TENTANG KEPARIWISATAAN SEBAGAI DASAR PEDOMAN DALAM PENGEMBANGAN PARIWISATA DI INDONESIA - Zulrijal Bushido Gani; Dani Arisandi DN; Anita Apriani (INTELIGENSIA MEDIA, 2024)
Indonesia has abundant natural wealth including tourism potential, most people in Indonesia whose regions have tourism potential have not been able to develop their tourism potential independently. Without realizing it, the current laws and regulations regarding tourism can be used as guidelines in developing tourism. This research is the basis for forming a guideline that can be used by the community to develop tourism potential independently. The research method used is systematic interpretation and legal reasoning by interpreting existing laws and regulations and then drawing conclusions about these regulations. The research results show that Law Number 10 of 2009 concerning tourism can be developed and used as a basic guideline in developing the tourism potential of a region independently by the community